Penguatan Peran Keluarga dalam Pencegahan Anemia pada Wanita Usia Subur - Nyna Puspita Ningrum; Nina Hidayatunnikmah; Desta Ayu Cahya Rosyida; Solichatin Solichatin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Anemia among women of reproductive age (WRA) remains a significant health problem affecting reproductive health and future generations. Limited knowledge and family involvement in anemia prevention were the main reasons for conducting this community service program. The aim was to improve knowledge and empower families in preventing anemia among WRA. The method involved health education through counseling, interactive discussions, and evaluation using pre-test and post-test. The results showed an increase in participants’ knowledge scores from 55.2 to 86.7 (57% improvement), along with positive changes in family attitudes and behaviors in supporting iron supplementation and nutritious diets. This program demonstrates that family-based education is effective in preventing anemia. Therefore, family involvement plays a crucial role in promoting sustainable health improvement among women of reproductive age.